2019
DOI: 10.3389/fnbeh.2018.00287
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Environmental Enrichment Elicits Behavioral and Physiological Dysregulation in Female Rats

Abstract: Chronic stress drives behavioral and physiological changes associated with numerous psychiatric disease states. In rodents, the vast majority of chronic stress models involve imposition of external stressors, whereas in humans stress is often driven by internal cues, commonly associated with a sense of loss. We previously exposed groups of rats to environmental enrichment (EE) for a protracted period (1 month), followed by removal of enrichment (ER), to induce an experience of loss in male rats. ER enhanced im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 34 publications
10
27
0
Order By: Relevance
“…Although both SD and EE animals were subjected to the deprivation of the social component, social isolation impacted the cognitive performance in EE mice more negatively. This is consistent with data showing that loss of enrichment changes the behavioral and physiological phenotypes of animals that had been exposed to long-term EE (Morano et al, 2019). Specifically, single housing following prolonged EE exposure was associated with increased weight gain, elevated helplessness and passive coping behaviors, and blunted hypothalamic-pituitary-adrenocortical activity (Morano et al, 2019; Smith et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although both SD and EE animals were subjected to the deprivation of the social component, social isolation impacted the cognitive performance in EE mice more negatively. This is consistent with data showing that loss of enrichment changes the behavioral and physiological phenotypes of animals that had been exposed to long-term EE (Morano et al, 2019). Specifically, single housing following prolonged EE exposure was associated with increased weight gain, elevated helplessness and passive coping behaviors, and blunted hypothalamic-pituitary-adrenocortical activity (Morano et al, 2019; Smith et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Although EE has been implicated in delaying the appearance of symptoms associated with certain brain disorders (Chourbaji et al, 2011; Herring et al, 2009; Van Dellen et al, 2000), it also makes individuals that are exposed to EE more vulnerable to its loss. Indeed, when the environment changes from being enriched to more impoverished (EE removal) behavioral alterations linked to depressive symptomology emerge (Morano et al, 2019; Smith et al, 2017). Moreover, these behavioral changes are accompanied by dysregulation of the hypothalamus-pituitary-adrenal axis activity in female rats (Morano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, multiple CBT sessions are typically required before patients begin seeing significant improvements in pain sensitivity, suggesting that increasing the duration of exposure to EE may be required to prevent stress‐induced pain behavior. Several reports showed that housing animals in SH cages, after being exposed to EE, induces a depressive‐like phenotype . In this regard, our animals did not develop visceral or somatic hypersensitivity after being housed in SH at the end of the WAS period.…”
Section: Discussionmentioning
confidence: 74%
“…These findings highlight the difficulty in dissociating the effects of EE from parental care to test if enrichment exposure during a particular developmental period is sufficient to offset the long-term effects of MIA in offspring. This task is challenged further by data showing that EE removal (and replacement into SD conditions) may simulate the experience of loss, inducing a depressive-like pheonotype (Smith et al, 2017;Morano et al, 2019). When EE is removed from dams, this may increase maternal care as a form of stimulation replacement (Rosenfeld and Weller 2012;Cutuli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%